2020
DOI: 10.3390/s20174736
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of the Complete Closed Mesh Model of Rail-Surface Scratch Data for Online Repair

Abstract: Rail surface scratching occurs with increasing frequency, seriously threatening the safety of vehicles and humans. Online repair of rail-surface scratches on damaged rails with scratch depths >1 mm is of increased importance, because direct rail-replacement has the disadvantages of long operation time, high manpower and high material costs. Advanced online repair of rail-surface scratch using three-dimensional (3D) metal printing technology such as laser cladding has become an increasing trend, desperately … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 34 publications
(52 reference statements)
0
4
0
Order By: Relevance
“…The data can be converted to the XZ plane reference system to focus on the change of the depth information z, which is convenient for the acquisition of the contour information. As shown in Figure 2, Guo et al 38 used the random sample consensus (RANSAC) algorithm to fit the contour shape of the rail geometric section, and used the distance threshold comparison to screen out the abnormal contour point cloud. Cao et al 5 proposed a dynamic interval fitting curve detection algorithm based on line-structured light.…”
Section: Based On Point Cloud Outlinementioning
confidence: 99%
See 1 more Smart Citation
“…The data can be converted to the XZ plane reference system to focus on the change of the depth information z, which is convenient for the acquisition of the contour information. As shown in Figure 2, Guo et al 38 used the random sample consensus (RANSAC) algorithm to fit the contour shape of the rail geometric section, and used the distance threshold comparison to screen out the abnormal contour point cloud. Cao et al 5 proposed a dynamic interval fitting curve detection algorithm based on line-structured light.…”
Section: Based On Point Cloud Outlinementioning
confidence: 99%
“…Extraction and fitting of point cloud contour. 38 introduced M estimation and ADF registration distance error function for the interference of noise points on registration.…”
Section: Based On Template Registrationmentioning
confidence: 99%
“…Reference [ 21 ] aimed at bridging the research gap found in the field of rail surface scratching data, where only a limited number of studies have addressed the issue of complete closed mesh model. The paper proposed a model based on a novel triangulation algorithm relying on the topological features of the point-cloud model (PCM) of scratch data.…”
Section: Analytics and Predictionmentioning
confidence: 99%
“…Its most important application is to repair high-value equipment, which can greatly save cost compared to buying another brand new, and, at the same time, the repaired work piece has at least the same performance to the original. Therefore, laser-cladding technology can be used in repairing the hard facing of turbine blade [2][3][4][5][6][7][8], forging die [9][10][11], as well as in various material processing industries for complex curved surface generating [12][13][14][15], and repairs of rail-surface scratch [16], artificial joints in medical treatment [17], broken gears [18], and worn sprockets [19].…”
Section: Introductionmentioning
confidence: 99%